Am I intruding? Developing a conceptualisation of advertising intrusiveness. Issue 9 (13th June 2018) - Riedel, Aimee S.; Weeks, Clinton S.; Beatson, Amanda T.
ABSTRACT: This study develops a conceptual framework of advertising intrusiveness that extends previous research on the topic by examining both drivers and consequences. To achieve this, the work draws on in-depth interviews with 29 adult consumers who report experiencing intrusive advertising in their daily lives. Three drivers of advertising intrusiveness are identified – temporal disruption, visual disruption and flow disruption – along with three consequences – emotional response, behavioural response and cognitive response. From these drivers and consequences, a conceptual framework of advertising intrusiveness is developed based on ideas about psychological reactance. Based on this framework it is proposed that, while all advertisements might ultimately be perceived as intrusive, an advertisement's characteristics, which are the identified subcomponents of the drivers of intrusiveness, exacerbate the resultant consequences.